Penerapan Sistem Keamanan (Firewall) Pada Jaringan Smart Home - Batubara, Algazali Raihan; Faisal, Ilham; Lubis, Imran (Forum Kerjasama Pendidikan Tinggi, 2025)
Currently, technological developments are increasingly advanced and developing, technological developments that are very rapid with the development of the times to meet human needs. One of them is the need for safe and comfortable home technology. The application of technology in the house is to use the concept of smart home by using firewall network security. Firewall on a smart home network is a concept where Internet of Things devices are safe from hacking by unknown people and cannot be controlled by other smartphone devices. Simulation is an important part of the application of the concept that will be carried out, especially to find out that research and studies are carried out using the simulation method as a way to solve problems. Cisco Packet Tracer 7.3 is an application that can help in terms of simulating Internet of Things devices. The results obtained from the firewall security concept simulation are that in the use of IoT devices such as house doors, windows, garages, lights, webcams and air conditioners are guaranteed to be secure because the devices that have permissions that can be connected.